LEKSIKON MAKIAN DALAM PERTUTURAN BAHASA INDONESIA: KAJIAN SOSIOLINGUISTIK - Ridha Mashudi Wibowo (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2020)
This research reveals the use of swear words in Indonesian language speech, including cursing, the referent of swear words, the type of target substance, the factors that influence the use of swearing, and gender: the data analysis used comparative, matching, and introspection methods with a socio pragmatic lens. Speaking pattern is used to know about the factors behind using the swear words. The study results are that the form of the swearing lexicon consists of words, phrases, and clauses. The shorter the form of swearing, the more expressive the name of curses is. The swear words referred to the body, nature, activity, animal, profession, artist/character, food, spirits, kinship, ethnicity, and hometown. The target substance to which abuse is aimed at ignorance, abnormality, something cursed, unlucky, and disgusting. The swear lexicon is spoken more often by men than women.